Mastering the Charts Framework in SwiftUI 4 & iOS 16. (Packt Publishing, 2022)
Apple unveiled a brand-new data visualization framework called Charts Framework at the Worldwide Developers Conference 2022. Charts enable developers to easily compose complex data visualizations with a few lines of code. The Charts view for SwiftUI is simple to integrate as any other view, so your data drives the changes for data visualization. Charts Framework is compatible with all Apple platforms, including iOS, iPadOS, macOS, and watchOS. This course explores the new Charts Framework using SwiftUI 4 and iOS 16. We will create practical examples and explore options to configure and use charts framework to match the app theme. You will learn about Charts Framework and SwiftUI 4 features and understand various creatable simple charts in SwiftUI and different markers that spruce up charts and more advanced concepts like the multi-series charts in SwiftUI, chart customization, and finally range area charts and empty state charts. Upon completion of this course, you will be adept in creating basic and multi-series charts. You will customize charts suited to your data visualization requirements and develop complex stacked, Candlestick, and combined charts and apply markers to enhance your chart data presentation. What You Will Learn Learn about Apple's Charts Framework in detail Understand the new features introduced in SwiftUI 4 Know about the new features introduced in iOS 16 Learn to apply data visualization techniques in iOS 16 using SwiftUI 4 Learn to build applications with data visualization in iOS 16 Learn about the different kinds of charts available in the Charts Framework Audience This intermediate- to advanced-level course caters to developers seeking to learn about Apple's newly introduced Charts Framework at WWDC 22. This course is intended for developers who want to incorporate data visualization into their apps, starting with iOS 16 and higher. It is also an ideal course for developers who want to include data visualization in their apps using SwiftUI. To garner the best benefits of this course, previous knowledge of SwiftUI and iOS programming is required. About The Author DevTechie LLC: DevTechie LLC offers courses where we learn by doing and find practical approaches to solve common problems. DevTechie LLC has 40+ years of combined experience in developing apps and software for big tech companies to small start-ups. They believe in sharing the knowledge gained over the years and invite you to join them on this journey. DevTechie LLC covers end-to-end development for mobile, web, backend, data science, and machine learning.